Assessing National Health Research System in a resource-limited setting: Insights from Indonesia - Tommy Dharmawan; Deandra Ardya Sutoyo; Fona Qorina; Nico Gamalliel; Mohammad Kurniawan; Dian Kusuma; Ahmad Fuady (PLoS ONE, 2026)
High-quality health research is essential for evidence-based policymaking and health system strengthening. Indonesia has undergone major reforms in its health research governance. However, the country’s National Health Research System (NHRS) remains insufficiently mapped. This study aimed to assess the current status of Indonesia’s NHRS using the WHO framework, which includes four domains: governance, financing, creating and sustaining resources, and producing and using research. A qualitative approach was employed, combining an expert panel discussion and key informant interviews with 13 participants consisting of national and subnational stakeholders from government agencies, research organisations, and universities from May to December 2024. Data were analysed using the Framework Method guided by the NHRS framework and supplemented by the WHO Questionnaire on Country Resources for Health Research. This study found that, despite progress in Indonesia’s NHRS, weak governance, particularly poor coordination between national and subnational levels, remains the main challenge. Overall, the system is still fragmented, even though formal structures and institutions are in place. Governance is characterised by a highly centralised, top-down approach to agenda setting, with limited engagement of local institutions. Research financing is mainly programmatic and proposal-based, aligned with national priorities, but is constrained by limited sustainable domestic funding and unequal access to funding. In terms of resources, advanced research infrastructure and growing international collaboration indicate national commitment to health research; however, mismatches between infrastructure and human resource capacity persist. Finally, although research production and utilisation focus on measurable outputs and are supported by mechanisms for evidence use, effective pathways for translating research into policy and practice remain limited. Improving Indonesia’s health research system calls for an integrated national research agenda, well-defined institutional roles, and streamlined coordination between national and regional levels.